Western sanctions against Russia and their impact on Trade Finance - Alesya Mitsura (2016)
Sanctions have always been a popular tool of foreign policy, capable of bringing about a desirable change in the behaviour of the country accused of violating a treaty or international law. Among all the existing types of sanctions, economic restrictive measures gained in importance in recent years, which led to their frequent use on a global scale. Although quite effective, economic sanctions often fail to achieve their goals, while leaving tremendous costs for both the states engaged into the conflict as well as their allies. These diplomatic and economic costs entail an overall deterioration of long-standing relationships of the involved parties, thus contributing to their isolation. All this leads to negative consequences for international trade, which is considered to be a driver of growth, economic prosperity and development.